PENGARUH MODEL PEMBELAJARAN DAN KEMAMPUAN MOTORIK TERHADAP HASIL BELAJAR LARI JARAK PENDEK (Studi Eksperimen di SMP Negeri 34 Kerinci) - Anggil Jufinda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to examine the influence of model of learning and motor skills for learning outcomes sprint seventh grade students of SMP Negeri 34 Kerinci. The research was conducted in SMP Negeri 34 Kerinci, this research uses experimental methods, the design of treatment by the level of 2x2. Samples were involved in this study were 64 students who joined in the two treatment groups, the number of samples of each group of 64 people belonging to the high motor skills and motor skills are low. Data analysis techniques using Anova (analysis of variance). The results of this study concluded that; learning outcomes sprinting for a given group of students with learning model creative play better overall than the group of students treated with cooperative learning model. There is no interaction between the learning model with motor skills for learning outcomes sprint. For students who have a high motor skills, learning outcomes sprinting through the application of creative play learning model is better than the model of cooperative learning. For students who have poor motor skills, learning outcomes sprinting through the implementation of cooperative learning model. better than learning model creative play.